(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
COVID-19 is characterized by a high risk of severe course and death in patients with comorbid pathology. Doctors are faced with the task of assessing the complex of anamnestic data and clinical symptoms in a short time in order to make a decision on the need to hospitalize a patient with COVID-19. At the same time, the predictors indicating an unfavorable course of COVID-19 have not been sufficiently studied. The factors contributing to the deterioration of the patient’s condition and leading to an unfavorable outcome have also not been sufficiently studied [Moreno-Pérez O. et al., 2020; Zou X., et al., 2020].